Water remediation by biosurfactant preparation of Rhodococcus erythropolis IMV Ac-5017 in presence of Cu2+ - Sofіlkanich (Morozova), Anna; Filyuk, Iryna; Pirog, Tatiana (My University, 2012)
It was showed that the oil destruction degree have increased significantly in presence of Cu2+ and surfactant preparation of Rhodococcus erythropolisІМV Ac-5017 strain. The oil destruction intensification in presence of Cu2+ could be caused by Cu2+positive influence on alcanehydroxylase activity in ІМV Ac-5017 strain, as well as in indigenous microflora.
Keywords: кафедра біотехнології і мікробіології